Price, Quality of Service and Promotion Toward Multifilament Tate Purchase Decisions At PT United Rope: Price, Quality of Service and Promotion Toward Multifilament Tate Purchase Decisions At PT United Rope - Wantoni Wantoni; Andrew Andrew; Setio Susanto; Fernando Fernando; Indra Sensiano (Jurnal Mantik, 2020)
This research was conducted at PT United Rope. The purpose of this study was to examine and analyze the effect of Price, Service Quality and Promotion on Purchasing Decisions of Multifilament Tate at PT United Rope. There is a decrease in purchasing decisions caused by Price, Service Quality and Promotion. This research approach is based on a quantitative approach. The population in this study amounted to 214 customers and the number of samples in the study were 139 customers. The sampling technique used was random sampling. The results of the calculation of the partial hypothesis testing showed that the price had a positive and significant effect on the purchasing decision of the multifilament tate at PT United Rope. The results of the calculation of the partial hypothesis testing obtained that service quality has a positive and significant effect on the multifilament tate purchasing decision at PT United Rope. The results of the calculation of the partial hypothesis testing obtained that promotion has a positive and significant effect on the purchasing decision of the multifilament tate at PT United Rope. The results of the calculation of hypothesis testing simultaneously obtained that price, service quality and promotion have a positive and significant effect on multifilament tate purchasing decisions at PT United Rope. The coefficient of determination test results obtained an Adjusted R Square value of 0.381, this means 38.1% of the variation in the dependent variable, namely the purchase decision which can be explained by the variation of the independent variable while the rest is 61.9% (100% - 38.